2021
DOI: 10.1177/20571585211018353
|View full text |Cite
|
Sign up to set email alerts
|

Customising clinical studies for the new nursing generation

Abstract: Nursing education in the Nordic countries follows the European Union directive requirements, and clinical studies for nursing students in the Nordic countries have many similarities. Now a new generation of students with different needs and characteristics is entering the nursing profession. The faculty, teachers and nurses will face challenges in meeting this new generation’s needs. The primary aim of this discussion paper is to explore and compare the current clinical studies in the five Nordic countries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Designing and applying educational models that support different generations’ learning processes is complex and challenging. We recognise Gunnarsdottir et al's 1 emphasis on structured reflection as a strategy for assessing, yet also teaching and learning clinical nursing skills. However, reflection involves exploring clinical experiences through thoughts, feelings and beliefs, which, though important for professional development, make the reflection subjective.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Designing and applying educational models that support different generations’ learning processes is complex and challenging. We recognise Gunnarsdottir et al's 1 emphasis on structured reflection as a strategy for assessing, yet also teaching and learning clinical nursing skills. However, reflection involves exploring clinical experiences through thoughts, feelings and beliefs, which, though important for professional development, make the reflection subjective.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, student follow-up and assessments must be interlinked beyond the single period of a clinical placement. Finally, our Nordic colleagues’ 1 suggestions and our reflections have demonstrated that there is a need for longitudinal research exploring different approaches and their suitability for current and future generations of nursing students.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…9 In this issue we are also publishing our first Nordic collaborative paper. Gunnarsdottir et al 10 are raising the need to develop and implement different types of strategies for teaching clinical skills among the new generations of bachelor nursing students who have grown up in a digital world. These students will have other needs for learning compared to previous generations.…”
mentioning
confidence: 99%